2004
DOI: 10.1103/physrevb.70.184123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short-range and long-range order on the evolution of the morphotropic phase boundary inPb(Zr1xTix)

Abstract: The local structures of rhombohedral, monoclinic, and tetragonal phases across the morphotropic phase boundary (MPB) of Pb͑Zr 1−x Ti x ͒O 3 are discussed in terms of the progression from short-range to long-range and back to short-range structural order. It is shown that, provided one considers the structures on a suitably small length scale, all three phases can be considered to be monoclinic at the local level and that there need not be any discrete phase boundaries across the MPB. Electron diffraction exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
137
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 54 publications
18
137
0
Order By: Relevance
“…With the refinement of anisotropic displacement ellipsoids they showed, that disordered Pb cation displacement could still show a rhombohedral structure on average. This idea was extended by Glazer et al 9 to the tetragonal side across the MPB. They suggested that PZT follows a composition dependent progression from short range to long range and back to short range order by crossing the MPB.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…With the refinement of anisotropic displacement ellipsoids they showed, that disordered Pb cation displacement could still show a rhombohedral structure on average. This idea was extended by Glazer et al 9 to the tetragonal side across the MPB. They suggested that PZT follows a composition dependent progression from short range to long range and back to short range order by crossing the MPB.…”
Section: Introductionmentioning
confidence: 83%
“…2͑c͔͒ and the order parameters in Fig. 4 the theory of Glazer et al 9 could be considered: at the MPB the local ordering of Pb displacements is extended to long range order of a size sufficient that diffraction techniques see a distinct phase of monoclinic symmetry, which was reported by Schierholz et al for undoped PZT. 18,19 The domain structures in PLZT 54/46 have a size of several nanometers and the characteristics of a tetragonal microstructure but compared to PZT 13 no superordinated microdomain structures are visible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was explained by displacing the Pb atoms away from the rhombohedral threefold axes to create local monoclinic structures 22 that averaged to an overall rhombohedral symmetry. On the basis of this assumption, Glazer et al 23 further proposed that the different average structures of PZT (R, M and T) could all be described in terms of local monoclinic ordering. Near the MPB region, the formation and the growth of these nanoscale regions may then account for the enhanced piezoactivity, in support of a domain-controlled contribution to the high piezoelectric properties 24,25 .…”
mentioning
confidence: 99%
“…6,7 Finally, the prototypical MPB in this lead-based piezoelectric material is described not as a sharp border, with all three phases providing a monoclinic distortion. 8 Although the issue is not clearly settled, MPBs are being sought as a starting point for identifying lead-free piezoceramics. 4,9 For example, the solid solution of ͑1−x͒Bi 0.5 Na 0.5 TiO 3 -xBaTiO 3 has been shown to exhibit useful piezoelectric properties at compositions near x = 0.06-0.07.…”
mentioning
confidence: 99%